2012
DOI: 10.1038/ncomms1893
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma induction by ultraviolet A but not ultraviolet B radiation requires melanin pigment

Abstract: Malignant melanoma of the skin (CMM) is associated with ultraviolet radiation exposure, but the mechanisms and even the wavelengths responsible are unclear. Here we use a mammalian model to investigate melanoma formed in response to precise spectrally defined ultraviolet wavelengths and biologically relevant doses. We show that melanoma induction by ultraviolet A (320–400 nm) requires the presence of melanin pigment and is associated with oxidative DNA damage within melanocytes. In contrast, ultraviolet B radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
294
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 286 publications
(315 citation statements)
references
References 58 publications
17
294
1
3
Order By: Relevance
“…Concurrent with existing literature proposing 2 independent pathways to melanomagenesis corresponding to induction by UVA and UVB irradiation, respectively, the study found that albino mice on the same genetic background developed fewer tumors than their pigmented counterparts following UVA irradiation. There were no significant differences between the mouse model tumorigenesis following UVB exposure (34). In line with current understanding that aberrant melanin synthesis is indeed associated with an increase in oxidative stress (35), the authors proposed that the increase in melanomagenesis observed in black mice was a result of dysregulated melanin synthesis induced by UVA exposure.…”
Section: Discussionsupporting
confidence: 60%
“…Concurrent with existing literature proposing 2 independent pathways to melanomagenesis corresponding to induction by UVA and UVB irradiation, respectively, the study found that albino mice on the same genetic background developed fewer tumors than their pigmented counterparts following UVA irradiation. There were no significant differences between the mouse model tumorigenesis following UVB exposure (34). In line with current understanding that aberrant melanin synthesis is indeed associated with an increase in oxidative stress (35), the authors proposed that the increase in melanomagenesis observed in black mice was a result of dysregulated melanin synthesis induced by UVA exposure.…”
Section: Discussionsupporting
confidence: 60%
“…Some reports claimed that UVA (320-380 nm) is the main cause of melanin synthesis and also melanoma appearance. This mechanism is related to reactions involving directly melanin, as the pigment absorbs the energy from the radiation and originates free radicals and other injurious species [158]. On the other hand, other reports indicate that UVB (280-320 nm) seems to initiate melanoma in a pigmentindependent manner, associated with a direct damaging action of that radiation on DNA [159].…”
Section: Melanin Functionsmentioning
confidence: 99%
“…Another important parameter that may affect the distribution of UVA-mediated DNA degradation products is cell type. This was recently illustrated for melanocytes that are more susceptible than other cell types to UVA-induced oxidatively generated damage to DNA both as isolated cells (89,116) and in pigmented mice (117). A summary of the main information available on the distribution of DNA damage generated upon exposure of cells to UVB and UVA radiations is provided in Fig.…”
Section: Uva-mediated Oxidatively Generated Dna Damage In Cellsmentioning
confidence: 99%